THE ROLE OF AZERBAIJAN CLASSICAL MUSIC IN FORMING THE VIRTUE OF INTERNATIONALITY IN STUDENTS. - E. Qabilova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article talks about the history of Azerbaijani classical music, the art of Mugam, and the formation of the virtue of internationality in students through Azerbaijani classical music.